An Asynchronous, Distributed Implementation of Mobile Ambients - Fournet, Cédric; Levy, Jean-Jacques; Schmitt, Alan (Proceedings of IFIP TCS 2000, LNCS 1872, 2000)
We present a first distributed implementation of the CardelliGordon’s ambient calculus. We use Jocaml as an implementation language and we present a formal translation of Ambients into the distributed join calculus, the process calculus associated with Jocaml. We prove the correctness of the translation.